2011
DOI: 10.1111/j.1365-2850.2011.01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed methods research in mental health nursing

Abstract: Mixed methods research is becoming more widely used in order to answer research questions and to investigate research problems in mental health and psychiatric nursing. However, two separate literature searches, one in Scotland and one in the USA, revealed that few mental health nursing studies identified mixed methods research in their titles. Many studies used the term 'embedded' but few studies identified in the literature were mixed methods embedded studies. The history, philosophical underpinnings, defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 20 publications
0
50
0
4
Order By: Relevance
“…A broad constructivist framework guided this study where language and meaning connect the experience as shared to its context [19]. A qualitative approach was most appropriate for this study to allow for an in depth exploration of the complexity of human experience and helps build a comprehensive understanding of patients’ choices and influencing factors surrounding alcohol use, potential for changes in behavior, and the impact of the ICU environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A broad constructivist framework guided this study where language and meaning connect the experience as shared to its context [19]. A qualitative approach was most appropriate for this study to allow for an in depth exploration of the complexity of human experience and helps build a comprehensive understanding of patients’ choices and influencing factors surrounding alcohol use, potential for changes in behavior, and the impact of the ICU environment.…”
Section: Methodsmentioning
confidence: 99%
“…Purposeful sampling was used to identify information-rich individuals who met criteria for an AUD within the context of an acute medical ICU admission, and who were willing to share detailed knowledge about their choices and perceptions about alcohol, its use and its relationship to their health. Adequacy of the sample size was based on the quality of data and nature of shared experiences [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Some reviews have also found low numbers of mixed methods studies in primary care [22], mental health nursing [21], and health services research [18]. In comparison, other reviews suggest mixed methods are used more often: one review of UK-funded health services research found that 18% of studies are mixed methods [17]; nursing and education journals publish more mixed methods studies (16%) than psychology and sociology journals (6%) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have described the prevalence and quality of mixed methods studies in health services research [16][17][18], social and behavioural sciences [19,20], and various biomedical disciplines [21][22][23]. The purpose of this review was to provide a critical overview of the current state of mixed methods research in CAM.…”
Section: Introductionmentioning
confidence: 99%
“…Today, however, the most commonly used term is "mixed methods". [3][4][5] Mixed methods is recommended when one of the four following scenarios is evident: 1) When very little is known about a new concept, a qualitative approach can be used before a quantitative approach; 2) when findings from a research approach can be better interpreted by using findings from the other approach; 3) when a sole approach is not sufficient to generate meaningful findings; and 4) when quantitative findings can be enriched by qualitative findings. 2,4 Oftentimes with mixed methods, results from one method can help identify appropriate participants to be questioned for richer information.…”
Section: -3mentioning
confidence: 99%